The Ephemeral Concept of Parasitic Commercial Practices in the EU - Radka MacGregor Pelikánová (Institute of Economic Research (IER), 2017)
Research background: It has been one decade since the transposition deadline regarding the Unfair Commercial Practices Directive. The EUs growth strategy, Europe 2020, and all EU member states are committed to smart, sustainable, and inclusive growth, to the single internal market and to R&D leading to innovations. These positive priorities, however, often conflict with one another. The EU crossed the Rubicon and decided to harmonize the protection against parasitic commercial practices hurting intellectual property and consumers. Is this appropriate, effective and efficient? Purpose of the article: The primary purpose of this article is to assess the appropriateness, effectiveness and efficiency of the EU harmonization of the ephemeral concept of parasitic commercial practices. The secondary purpose is to assess approach(es) of the EU and EU member states to this overlap of the competition and intellectual property regimes. The third purpose is to assess the feasibility of the integrative harmonization in this arena. Methodology/methods: The multi-disciplinary nature of this article, and its three purposes, leads to the employment of Meta-Analysis, of the critical comparison of laws and the impact of their application, to the holistic perception of historical and national contexts, and to case studies. The primary sources (field search) and secondary sources (literature) are explored and the yield knowledge and data are confronted with the explored cases. The dominating qualitative research and data are complemented by the quantitative research and data. Findings & Value added: The Unfair Commercial Practices Directive harmonizes the protection of various issues, including the ephemeral concept of parasitic commercial practices. The set trio of purposes leads to a conclusion that this overlap of competition and intellectual property protection is highly sensitive and nationally particular. EU integration in this sphere is needed, but the undertaken harmonization is not fully effective and efficient, and perhaps even not appropriate.
Keywords: D18; K22; M38; O34; 330; Unfair Commercial Practices Directive; Unfair Competition; Intellectual Property; Innovation; Consumers